A LACANIAN ANALYSIS OF ORHAN PAMUK’S ‘THE RED-HAIRED WOMAN’ - Salih, Huda (Humanities Journal of University of Zakho, 2024)
Orhan Pamuk's novel The Red Haired Woman delves into the complexities of identity desire and the unconscious mind through the character of Cem. By employing a Lacanian analysis, this qualitative research paper aims to explore how Cem's psyche is shaped by the interplay between the Symbolic, the Imaginary, and the Real. Drawing from Lacanian concepts such as the mirror stage castration anxiety and the Oedipus complex, this paper sheds light on the underlying psychological factors influencing Cem's actions and relationships within the novel. By delving into these Lacanian concepts we gain a deeper understanding of Cem's character and the overall themes explored in Orhan Pamuk's novel. The novel invites the readers to contemplate the intricacies of the human psyche and the perpetual pursuit of identity and desire in the face of societal constraints. Pamuk’s narrative, set against the backdrop of Turkey’s socio-political landscape, intricately weaves together themes of fatherhood, patricide, and the search for meaning. By unraveling the symbolic and imaginary dimensions of the narrative, this study illuminates the novel's deeper layers of meaning. It offers insights into the human condition as portrayed through Pamuk’s literary lens. Pamuk intricately intertwines themes of patricide, fatherhood, and existential quest, providing fertile ground for a Lacanian reading.